Succession of Vegetation Types in the Tons Valley of the Garhwal Himalayas - Gupta, R. K.; Singh, J. S. (Indian Forester, 1962)
The Tons valley lie. Between 30Â°55’ and 31Â°28’ N. latitude and 77Â°22’ and 78Â°38’ E. longitude in the Garhwal Himalayas. In the present paper physical features, climate, rock and soil, forest biota and vegetation of the area are described. The vegetation has been divided into various zones according to the altitude. Ecological status of vegetation types in each zone is discussed. Oaks form the climatic climax at the lower altitudes by Quercus incana Roxb. And at the higher altitudes by Quercus semecurpifolia Smith. Pinus roxburghii Sarg. Forests occurring in the subtropical zone are considered to be bioedaphic in nature forming a secondary succession to the oak climax and may be considered as pre-climax or sub-climax in Clement’s terminology.